2012
DOI: 10.1021/jp300506g
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermal Oxidation of Si(100)2×1 Surfaces: Effect of Growth Temperature

Abstract: Using reactive molecular dynamics simulations based on the ReaxFF potential, we studied the growth mechanism of ultrathin silica (SiO2) layers during hyperthermal oxidation as a function of temperature in the range 100–1300 K. Oxidation of Si(100){2 × 1} surfaces by both atomic and molecular oxygen was investigated for hyperthermal impact energies in the range of 1 to 5 eV. Two different growth mechanisms are found, corresponding to a low temperature oxidation and a high temperature one. The transition tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 53 publications
5
56
0
Order By: Relevance
“…21 Theoretical studies will be required to obtain detailed physical insight into the origin of O 2 adsorption. [48][49][50] …”
Section: +mentioning
confidence: 99%
“…21 Theoretical studies will be required to obtain detailed physical insight into the origin of O 2 adsorption. [48][49][50] …”
Section: +mentioning
confidence: 99%
“…We do see the presence of some of these suboxides even in the silicon oxide region III, which can be related to possible presence of overcoordinated and under-coordinated Si atoms that were assumed to be found in this region as per simulations. 11 Also, it was reported that the observed silica region can be divided into surface and bulk regions. 36 In the present case, we refer to a surface silica region and a bulk silica region.…”
mentioning
confidence: 99%
“…11 Namely, due to the decreasing of interfacial stresses 42 in Region II, the mobility of oxygen atoms in the transition region increases. While the thickness of the transition region (Region II) is somewhat smaller in the simulation results, the ratio between the thicknesses at both investigated temperatures agrees quantitatively with the experimental result, at a ratio of about 1.3.…”
mentioning
confidence: 99%
See 2 more Smart Citations